Natural history of aggressive behaviour in dementia. - Keene, J; Hope, T; Fairburn, C; Jacoby, R; Gedling, K; Ware, C (1999)
OBJECTIVE: This article analyses changes in aggressive behaviour throughout the course of dementia. DESIGN: Prospective, 10 year, longitudinal study of aggressive behaviour in dementia, with autopsy follow-up. SETTING: Subjects with dementia, living at home with a carer, Oxfordshire, UK. PARTICIPANTS: Ninety-nine people with dementia (Alzheimer's disease and/or vascular dementia) who were living at home with a carer. MEASURES: At 4-monthly intervals, the carers were interviewed about the subjects and the subjects were assessed cognitively. Subjects' behaviour was assessed using the Present Behavioural Examination. This is an investigator-based, semi-structured interview consisting of eight main sections monitoring behavioural and psychological change. Eight different aspects of aggressive behaviour were assessed in detail and comparison made with other relevant factors. RESULTS: Verbal aggression is the most common and longest lasting form of aggressive behaviour. Aggressive resistance and physical aggression are most likely to persist until death. Intimate care is the main factor precipitating aggressive behaviour. There are no correlations between any type of aggressive behaviour and age, gender or time since onset of dementia. CONCLUSIONS: Aggressive behaviour creates problems for carers. In general, the physical types of aggressive behaviour are most prevalent in people with more severe dementia.